KONSTITUSIONALITAS USIA CALON PRESIDEN DAN WAKIL PRESIDEN DALAM PUTUSAN MAHKAMAH KONSTITUSI NOMOR 90/PUU-XXI/2023 - Fx. Valentino David Adison P; Bambang Arwanto (Causa: Jurnal Hukum dan Kewarganegaraan, 2024)
This research aims to analyse the differences in qualifications for presidential candidates across various countries and to reconstruct how the Constitutional Court Decision Number 90/PUU-XXI/2023 could be determined. Consequently, it offers an objective perspective on the differing qualifications of presidential and vice-presidential candidates in various nations and provides guidelines for Indonesia. It seeks to present a legal and ethical viewpoint regarding the decision-making process of the Constitutional Court in relation to Decision Number 90/PUU-XXI/2023 and assess its connection to the ideal duties and authorities of the Constitutional Court. The issues discussed in this journal can be addressed by establishing a law that governs the age restrictions for presidential and vice-presidential candidates, which serves not only as guidance but also delineates the authority of the Constitutional Court.